Інституційні форми взаємодії держави і приватного підприємництва - Скорик, Г. І. (Видавництво Національного університету “Львівська політехніка”, 2005)
Однією з найважливіших форм взаємодії держави і приватного підприємництва є співпраця влади з об'єднаннями підприємців. Тому в статті розглянуто деякі інсти- туційні форми такої взаємодії, шляхи і перспективи передачі ряду регулюючих функцій від держави до підприємницьких союзів (об'єднань).

One of the most important forms of co-operation of the state and the private enterprise is collaboration of state power with associations of businessmen. In the connection with it some institution forms of such co-operation, ways and prospect of transmission of some regulative functions, are considered from the state to the enterprise unions (associations) in the article.
Keywords: 338.242